Anton Mosimann: Cooking with Mosimann - 'The Cookbook of the TV series' - D, C (Petits Propos Culinaires, 1990)
Anton Mosimann: Cooking with Mosimann - 'The Cookbook of the TV series': Macmillan Papermac, London, 1989: 213 pp, numerous colour plates, £6.99.